Bioactivity of essential oils: a review on their interaction with food components - Perricone, Marianne; Arace, Ersilia; Corbo, Maria R.; Sinigaglia, Milena; Bevilacqua, Antonio (Frontiers in Microbiology, 2015)
Essential oils (EOs) are liquid preparations, produced from plant materials. Although EOs showed a promising bioactivity in vitro, they could interact in foods with some components (fats, proteins, carbohydrates) and pH, thus many authors have reported that a significant effect of EOs towards spoiling and pathogenic microorganisms could be achieved in vivo by using higher amounts of oils. Different methods can be used to assess the bioactivity of EOs (disk diffusion and agar or broth dilution methods); however, there is not a standardised test and researchers propose and use different protocols (evaluating the Minimal Inhibitory Concentration, studying the survival curves, analysis through the scanning electron microscopy, etc.). Thereafter, the scope of this review is a focus on interactions of EOs with proteins, carbohydrates, oils, NaCl and pH, as well as a brief description on the different protocols to assess their bioactivity both under in vivo and in vitro conditions.